2022
DOI: 10.1186/s12868-022-00689-w
|View full text |Cite
|
Sign up to set email alerts
|

Different paradigms of transcranial electrical stimulation improve motor function impairment and striatum tissue injuries in the collagenase-induced intracerebral hemorrhage rat model

Abstract: Background In the horizon of therapeutic restrictions in intracerebral hemorrhage (ICH), recently, non-invasive transcranial electrical stimulation (tES) has achieved considerable prosperities. Translational studies have postulated that transcranial direct current stimulation (tDCS) and the other types of tES remain potentially a novel therapeutic option to reverse or stabilize cognitive and motor impairments. Objective The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…These studies explored the neurophysiological mechanisms of tPCS. The findings of a study revealed that tPCS, similar to other tES techniques, significantly influenced motor disorders in collagenase‐induced intracerebral hemorrhage (Heidarzadegan et al., 2022). Another study suggested that tPCS can enhance the locomotor function of stroke rats by regulating the expression of microtubule‐associated protein around the ischemic penumbra (Wang et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These studies explored the neurophysiological mechanisms of tPCS. The findings of a study revealed that tPCS, similar to other tES techniques, significantly influenced motor disorders in collagenase‐induced intracerebral hemorrhage (Heidarzadegan et al., 2022). Another study suggested that tPCS can enhance the locomotor function of stroke rats by regulating the expression of microtubule‐associated protein around the ischemic penumbra (Wang et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 500 articles, including 498 studies from online databases and two studies (Alon et al., 2011; Heidarzadegan et al., 2022) from searching in the cited references of included studies. In the second stage, 204 articles remained after removing duplicates from the initial search result.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations